Characteristics of Musical Ability Development - Yunusov Odil Gaybullaevich; Khojamkulov Pirimqul (Zien Journals, 2022)
Music lessons are specific forms of manifestation of mental activity of the child's personality. The development of more musical hearing of students through musical abilities. The process of performing music lessons in secondary schools is one of the most important tasks
Keywords: art; national music; contemplation; musical contemplation; value